Reduced abstractness in Spanish-English translation: the case of property-denoting nouns - Espunya, Anna (Meta, 2020)
This study proposes an empirical methodology to test the hypothesis that translation from Spanish into English results in reduced abstractness. The semantic area focused upon is the attribution of properties to specific entities by means of abstract nouns. Two levels of abstractness, conceptual and grammatical, are considered. Conceptual abstractness is linked to the referential content of the nouns, while grammatical abstractness involves the reified expression of properties as nouns, as opposed to other word classes. The study classifies the translation correspondences for nouns ending in the suffix -idad in the Spanish novels by Manuel Vázquez Montalbán (1939-2003) Los mares del Sur and Tatuaje. Such property-denoting nouns contribute to the construal of point of view. The methodology combines a quantitative approach with a qualitative, text-analytic selection of relevant items. Results indicate that abstractness is mainly reduced on the grammatical level although instances of diminished conceptual abstractness can also be observed. Compliance with language preferences may be aligning with readability norms affecting the target product, crime fiction, to undo reification of properties (namely explicitation and simplification). The results underscore the need to include semantic parameters in studies of translation tendencies.